Sago Management Trade System in Merauke Regency - Adrianus; Sajriawati; Mani Yusuf; Reny Sianturi; Yosehi Mekiuw; Fajar Islam; Dewanto Talubun; Suwarjono (JURNAL AGRIMENT, 2026)
Sago is one of the strategic local food commodities in Indonesia that has great potential in supporting food diversification, especially in Merauke Regency. This study aims to find out the trading system of sago management in Merauke Regency. The method used in this study is a descriptive method with qualitative and quantitative approaches. The qualitative approach is used to describe the sago trading system, the pattern of relationships between business actors, the production process, processing, distribution, and the institutional roles involved. The results of the study show that the sago management business system in Merauke Regency is still dominated by the traditional system with indigenous peoples as the main producers, while distribution and marketing are centered on the local market. Sago processing began to develop from traditional to semi-modern methods so as to increase the efficiency, quality, and selling value of products. Sago has great economic potential as a source of local food and industrial raw materials, but its development still faces technological constraints, market access, capital, unstable prices, and land conversion. Therefore, government support, technological innovation, and strengthening of MSMEs are needed so that sago can become a leading commodity that supports food security and the welfare of the people of Merauke